A Novel SoC Design of Adaptive Stabilization Engine for Metastable PUF Source - Wan, Meng-Ting; Lin, Hao-Ting; Yang, Yu-Jyun; Fahier, Nicolas; Fang, Wai-Chi (IEEE International Symposium on Circuits and Systems proceedings, 2023)
An adaptive PUF source stabilization digital engine is proposed, applied to a symmetrical SR-latch structure for metastable PUF source, and implemented on TSMC 90nm process. In a global PUF system design, the stability of the PUF source directly affects the burden of error correction coding, as well as the required time and space resource consumption. According to the measurement and stability performance analysis of the PUF challenge and response results from 16 chips, although most of the PUF cells were having stable states, a non-negligible number of cells remained in oscillating states, in addition to major inter-chips differences for stability performances. Dark bit masking and Temporal Majority Voting(TMV) is a common and effective method to stabilize a PUF source but it involves a trade-off between stability and entropy loss. Stabilization with a fixed process design cannot achieve the best performance considering the large stability variations across different chips. We proposed an adaptive PUF stabilization processing engine that provides an enhanced TMV approach with the ability to stabilize the PUF source without reducing the expected number of PUF entropy. The PUF source raw bit error rate(BER) improved from 1.6e-2 to 1.7e-6 after stabilization.